Implementation of Punishment in An Efforts to Strengthen The Character of Students' Discipline - Mudillah Habibah; Feriska Listrianti (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2026)
Discipline is one of the character important things to do owned students in environment Islamic boarding school, however various form violation of regulations Still found so that effective coaching strategies are needed through application of punishment that is educational. Research This aim for analyze application of punishment in effort strengthening character discipline students in the Al Hasimiyah Region Cottage Nurul Jadid Islamic Boarding School. Research use approach qualitative with type studies case, involving 10 informants consisting of on administrator security and order, dormitory management, and students who have ever receive punishment, with technique data collection through interviews, observations, and documentation analyzed using interactive models through stages data reduction, data display, and data verification. Research results show that the punishment applied more nature educative than repressive, with form in the form of task cleanliness, memorization verses of the Qur'an, memorization prayer, assignment social and development special for violation repeated. The application of punishment is carried out in a way gradual and proportional in accordance level violation so that reflect principal justice in coaching. Most of students give response positive because punishment helps increase awareness and compliance to rules. In addition, it was found existence trend decline amount violation after implementation a more stringent punishment system structured and consistent. Success the implementation of punishment is supported by consistency administrators, mentoring after giving punishment, as well as environment Islamic boarding schools that support formation character discipline